Community-Driven Development, Collective Action and Empowerment: Effective Communication Matters (A Lesson from the KDP and the UPP in Indonesia) - Aryanta Nugraha (The Indonesian Journal of Communication Studies, 2010)
Community-driven development (CDD) has become the most important strategy of the World Bank’s development assistance for poverty alleviation. It supported propositions that more Participatory element in community-driven development would allow development process more inclusive to poor people, enhancing social cohesion based on trust and social capital and bring about collective action that considered necessary to solve poverty problem. This paper attempts to ex- plore the impacts of CDD to collective action and empowerment particularly in the context of Kecamatan Development Program (KDP) and Urban Poverty Project (UPP). Drawing literature study as supporting evidence, it argues that collective action and empowerment emerged from the KDP and the UPP has not achieved the substantial level to address poverty problem because there are inherent problems in the participatory development design and various social challenges. This paper, therefore, suggests that effective communication is needed in community development as it will enhance the community ownership feeling to the development rather than considering them- selves as solely the beneficiaries of the community development process